2010
DOI: 10.1039/b920199h
|View full text |Cite
|
Sign up to set email alerts
|

New discrete and polymeric supramolecular architectures derived from dinuclear Co(ii), Ni(ii) and Cu(ii) complexes of aryl-linked bis-β-diketonato ligands and nitrogen bases: synthetic, structural and high pressure studies

Abstract: New examples of nitrogen base adducts of dinuclear Co(II), Ni(II) and Cu(II) complexes of the doubly deprotonated forms of 1,3-aryl linked bis-beta-diketones of type [RC(=O)CH(2)C(=O)C(6)H(4)C(=O)CH(2)C(=O)R] (L(1)H(2)) incorporating the mono- and difunctional amine bases pyridine (Py), 4-ethylpyridine (EtPy), piperidine (pipi), 1,4-piperazine (pip), N-methylmorpholine (mmorph), 1,4-dimethylpiperazine (dmpip) and N,N,N',N'-tetramethylethylenediamine (tmen) have been synthesised by reaction of the previously re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…In the case of m-phenylene spaced ligands of the type H 2 L1 (Scheme I), reactions with divalent M(II) metals most often lead to dimetallic species of the type [M 2 (L1) 2 S x ] (S = solvent; x = 2 or 4), where the b-diketonates occupy equatorial coordination sites while the solvent ligands take axial positions [4][5][6][7][8]. On the other hand, trivalent M(III) ions favor the formation of neutral triple stranded dimetallic helicates with formula [M 2 (L1) 3 ] [9,10], as facilitated by the tendency of many of these metals to acquire octahedral coordination geometry.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of m-phenylene spaced ligands of the type H 2 L1 (Scheme I), reactions with divalent M(II) metals most often lead to dimetallic species of the type [M 2 (L1) 2 S x ] (S = solvent; x = 2 or 4), where the b-diketonates occupy equatorial coordination sites while the solvent ligands take axial positions [4][5][6][7][8]. On the other hand, trivalent M(III) ions favor the formation of neutral triple stranded dimetallic helicates with formula [M 2 (L1) 3 ] [9,10], as facilitated by the tendency of many of these metals to acquire octahedral coordination geometry.…”
Section: Introductionmentioning
confidence: 99%
“…It is a ditopic molecule which can coordinate the metal ion via one heteroatom, leaving the other free for linking to other molecules either as an electron pair donor [16][17][18][19] or as a hydrogen acceptor [20][21][22][23]. Our study concentrated on morpholine adducts of benzoylacetonates of divalent metals (M(bzac) 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…3 We, and others, have found that ligands incorporating more than one β-diketone motif react with selected metal ions to yield an array of metallo-supramolecular architectures with the products in many instances exhibiting a significant degree of predictability. 1,3,10 Structures generated with these ligands include helicates, [11][12][13][14] tetrahedra, 15,16 boxes, 17 capsules 18 and an unprecedented universal 3-ravel; 14 for example, the well defined coordination vectors of ligands L 1-3 produce neutral planar metallocyclic species of type [M 2 (L 1 ) 2 ] (1) 11,13,[19][20][21] [M 3 (L 2 ) 3 ] (2) 16,22 and the larger [M 3 (L 3 ) 3 ] (3) 23,24 upon reaction with selected divalent transition metals.…”
Section: Introductionmentioning
confidence: 99%